Estimation of the soil erodibility factor of a peri-urban catchment by group method of data handling and enhanced particle swarm optimization method - Kant, Chander; Majumder, Mrinmoy; Kumar Tyagi, Dharmendra; Prabhat Singh, Ashish (International Journal of Engineering and Technology, 2018)
Soil erosion has become a major deterrent in any watershed management program. The erodibility of the soil from the river banks has degraded watersheds all over the world. That is why in any watershed development programmers’ erodibility of soil becomes a significant design parameter. However, there is lack of efficient simulation model for estimation of soil erosion. The existing models are location sensitive and mostly empirical nature in the present investigation, the authors tried to estimate the soil erodibility factor of the USLE method with the help of Enhanced PSO. The data for development of model is generated by Normalized Design of Experiment method which assumes that maximum and minimum value can be represented by I and O respectively. The same model was developed with the help of GMDH also. As per the model matrices of GMDH model shows better reliability. The selected model was applied to predict soil erodibility factor for 21 no’s of location in west Tripura region. From the prediction and comparison with the actual data it was found that the selected models have an accuracy of 99.8% in predicted model and 89.8% in case study.